Risk-seeking, risky lifestyles and cyberstalking - what factors promote cyberstalking victimization among adolescents?: an empirical test of the self-control/risky lifestyle mediation hypothesis = Risikobereitschaft, riskante Lebensweisen und Cyberstalking - welche Faktoren begünstigen die Viktimisierung durch Cyberstalking bei Jugendlichen? : ein empirischer Test der Selbstkontrolle/riskanter Lebensstil Mediations-Hypothese - Bergmann, Marie Christine (Kriminologie - das Online-Journal, 2023)
The aim of this paper is to apply the self-control/risky lifestyle theory tothe risk of cyberstalking victimization amonga younger age group by using a representative student sample from Germany. Results show that cyberstalking victimization is experienced by 18.2% of the representative sample of ninth graders. Girls were more often victimized than boys. Only a minority solely experience cyberstalking whereas considerably more juveniles report having experienced both offline stalking and cyberstalking. The findings from the parallel multiple mediation models support the self-control/lifestyle theory and are consistent with a growing body of literature indicating thatlow self-control has a direct and indirect effect on the risk of experiencing cyberstalking. For both genders,riskseeking is significantly and positively associated with the risk of experiencing - both directly and indirectly - cyberstalking victimization.